Base-Free Catalytic Wittig-/Cross-Coupling Reaction Sequence as Short Synthetic Strategy for the Preparation of Highly Functionalized Arylbenzoxepinones - Pudnika, Linda; Domraceva, Ilona; Werner, Thomas; Zalubovskis, Raivis; Grandane, Aiga (Synthesis, 2021)
The facile synthesis of highly functionalized building blocks with potential biological activity is of great interest to medicinal chemistry. The benzoxepinone core structures commonly exhibit biological activity. Thus, a short and efficient synthetic route towards benzoxepine containing scaffold, which enables late stage modification was developed. Namely, base-free catalytic Wittig reactions enabled the synthesis of bromobenzoxepinones from readily available starting materials. Subsequent, Suzuki–Miyaura and Stille reactions proved to be suitable methods to access a variety of benzoxepinone diaryl derivatives by late stage modification in only three steps. This three-step reaction sequence is suitable for high throughput applications and gives facile access to highly complex molecular structures, which are suitable for further functionalization. The antiproliferative properties of selected arylbenzoxepinones were tested in vitro on monolayer tumor cell line A549. Notably, in this initial screening, these compounds were found to be active in the micromolar range.
Keywords: benzoxepinone; catalytic Wittig reaction; Stille reaction; Suzuki–Miyaura reaction; A549; cytotoxicity